TEACHERS' PERCEPTION ON THE INTEGRATION OF DIGITAL LITERACY IN TEACHING ENGLISH AS A FOREIGN LANGUAGE - Silvia Putri; Fauziah Fauziah; Zaiturrahmi Zaiturrahmi (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2026)
This study explores EFL teachers’ perceptions in integrating digital literacy into TEFL. As technology becomes increasingly vital in education, understanding how teachers adopt digital tools is essential. Using a qualitative case study approach, data were collected through interviews, classroom observations, and document analysis involving four English teachers. The findings reveal that teachers generally have a positive perception of digital literacy, recognizing its potential to enhance student engagement, improve language skills, and connect with students’ digital habits. The study concludes that integrating digital literacy effectively requires supportive policies, reliable infrastructure, and continuous professional development.